Refleksi Fenomena Judicialization of Politics pada Politik Hukum Pembentukan Mahkamah Konstitusi dan Putusan Mahkamah Konstitusi - Indra Perwira (The Constitutional Court of the Republic of Indonesia, 2016)
This paper aims to introduce the phenomenon of judicialization of politics in the treasury of legal thought in Indonesia. In addition, this paper also aims to reflect the presence of judicialization of politics in the Constitutional Court, either through legal policy on establishment of constitutional court or through its decisions. Theoretically, the phenomenon of judicialization of politics began to be known at the beginning of the 21st century characterized by the dependence of society to the court to resolve the issues related to morality, public policy, and political controversies. The presence of judicialization of politics can be reflected from the shift in the political settlement of the case which was originally made through political mechanisms to the settlement through a judicial mechanism. To see the phenomenon, this paper will explore the legal policy on establishment of the Constitutional Court. Through a historical perspective on the establishment, this paper would like to indicate that, in nature, the Constitutional Court is a political institution. In addition, this paper also analyzes the Constitutional Court decision in the case of judicial review on “Perpu” of the Corruption Eradication Commission (KPK) and the decision regarding the dispute Election East Java province in 2008, to show that the phenomenon of judicialization of politics has lived and practiced in the Constitutional Court as well.